Antibiotic Resistance in Pediatric Pneumonia Patients: Assessing Prevalence and Prescribing Practices - Maazullah; Muhammad Esa; Zul Kamal; Abid Ullah; Faiz-ur-Rahman; Waqar Ahmad Khan; Arsalan Khan; Muhammad Asghar Khan; Hamid Ali (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Antimicrobial resistance (AMR) has become a significant worldwide health issue, endangering public health through diminished opportunities for treatments, an increasing incidence of morbidity and mortality, and increasing healthcare costs. This study investigates the prevalence of antibiotic resistance, prescribing patterns and antibiotic responsiveness in pediatric pneumonia with an effort to highlight the urgent need to address this issue. This study assessed the antibiotic prescriptions, hospital longevity and treatment outcomes in 73 pneumonia patients. A total of 506 drugs were prescribed, with an average of 6.9 drugs per prescription, surpassing the recommended WHO standard of 1.6-1.8 drugs. Antibiotics accounted for 38.7% of the prescribed drugs (n=197). Injectable drugs, generic names, and drugs from the Essential Drug List (EDL) comprised 58.5%, 12.84%, and 95% of the prescriptions, respectively. The most common antibiotic combination was ampicillin-cloxacillin, prescribed to 33% of the patients, of which 84.5% of patients did not responded and switched to another drug combination. Ampicillin-cloxacillin-ceftazidime combination was prescribed to 14.6% of patients, however this combination received a non-response rate of 7.1%. Patients unresponsive to these regimens were switched to more efficacious antibiotics such as linezolid, vancomycin, amikacin, ceftriaxone, and cefotaxime. This study highlights the rapid emergence of antibiotic resistance in children with pneumonia, which is associated with their vulnerability to infections due to a compromised immune system. Empirical antibiotic therapy practices, which are frequently utilized in pediatric patients, have led to a rise in resistance to first-line antibiotics (amoxicillin-cloxacillin) used to treat pneumonia. In order to address this critical issue, collaborative efforts from healthcare professionals, policymakers, and the community will be required to raise awareness and promote appropriate antibiotic usage and combat the emergence of AMR in Pakistan.